American tourists in Cuba: Is the communist country a forbidden or a tainted fruit?. (January 2016) - Wilson, Jackson; Látková, Pavlína
Americans are the majority of tourists in the Caribbean, but the US embargo against Cuba prevents almost all American tourists from visiting Cuba. This study uses mixed methods to examine a group of American tourists' destination image of Cuba before and after a tour in Cuba. The American tourists in this study described Cuba as a forbidden fruit, a desirable destination that Americans are not allowed to or at least should not visit. On the positive side, travelling to Cuba was seen as a scarce opportunity that has the allure of the prohibited and the attraction of viewing communism from a previous era. Conversely, the image of Cuba was also tainted by the history of political antagonism with America and associated concerns about tourist safety, cost, and a limited market place. However, actual and potential changes in Cuba are likely to heavily impact the destination image in the near future.